(untitled) (Brazilian Journal of Radiation Sciences, 2023)
In this work we obtained experimental linear attenuation coefficients of polymer-based samples at diagnostic imaging energy range (15-150 keV) for eleven formulations candidates for tissue-equivalent materials (TEMs). TEMs is any material that simulates a human body part or human tissue in its interaction with radiation. In diagnostic radiology, the maximum difference between the linear attenuation coefficient of the TEMs and the target material should be no more than 5% in the energy range of interest. A polienergetic narrow beam was obtained using a tungsten target x-ray tube and CdTe detector. The densities of the samples were determined and compared with reference materials obtaining a maximum difference of 17%. The comparisons between the linear attenuation coefficient of the formulations and the respective reference materials for which they were initially designed, has demonstrated good correspondence over a wide energy range. Energy ranges in which the developed samples simulate other human tissues in addition to those initially considered were found, taken into account the criterion that the maximum difference between the linear attenuation coefficients does not exceed 5% is met. The results emphasize the possibility of production and characterization of TEMs to be used in the construction of imaging and dosimetry phantoms.